Aberrant Drp1-mediated mitochondrial division presents in humans with variable outcomes. (2nd August 2018) - Whitley, Brittany N; Lam, Christina; Cui, Hong; Haude, Katrina; Bai, Renkui; Escobar, Luis; Hamilton, Afifa; Brady, Lauren; Tarnopolsky, Mark A; Dengle, Lauren; Picker, Jonathan; Lincoln, Sharyn; et al.
Abstract: Mitochondrial dynamics, including mitochondrial division, fusion and transport, are integral parts of mitochondrial and cellular function. DNM1L encodes dynamin-related protein 1 (Drp1), a member of the dynamin-related protein family that is required for mitochondrial division. Several de novo mutations in DNM1L are associated with a range of disease states. Here we report the identification of five patients with pathogenic or likely pathogenic variants of DNM1L, including two novel variants. Interestingly, all of the positions identified in these Drp1 variants are fully conserved among all members of the dynamin-related protein family that are involved in membrane division and organelle division events. This work builds upon and expands the clinical spectrum associated with Drp1 variants in patients and their impact on mitochondrial division in model cells.